2021
DOI: 10.3390/v13081576
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Monooxygenases CYP6AY3 and CYP6CW1 Regulate Rice Black-Streaked Dwarf Virus Replication in Laodelphax striatellus (Fallén)

Abstract: The small brown planthopper, Laodelphax striatellus (Fallén), is an important agricultural pest that causes significant losses by sucking and transmitting multiple plant viruses, such as rice black-streaked dwarf virus (RBSDV). Insecticides are commonly used to control planthoppers and cause the induction or overexpression of cytochrome P450 monooxygenases (P450s) from the CYP3 and CYP4 clades after insecticide application. However, little is known about the roles of insecticides and P450s in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…( Liu et al, 2020 ; Pandian et al, 2020 ). Previous studies indicated that several P450 genes were involved in disease resistance in rice and barley ( Ameen et al, 2021 ; Zhang et al, 2021 ; Wang A. et al, 2022 ), implying their potential roles in maize disease resistance. Interestingly, we also found that 8 of 267 (4 of 115) co-DEGs belong to the ABC transporter superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…( Liu et al, 2020 ; Pandian et al, 2020 ). Previous studies indicated that several P450 genes were involved in disease resistance in rice and barley ( Ameen et al, 2021 ; Zhang et al, 2021 ; Wang A. et al, 2022 ), implying their potential roles in maize disease resistance. Interestingly, we also found that 8 of 267 (4 of 115) co-DEGs belong to the ABC transporter superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the degradation products of chlorophyll metabolism would serve antiviral function when binding to their receptor proteins ( 56 ). A recent study shows that the p450 related drug metabolism pathways can regulate the replication of plant virus in insect ( 57 ). In vertebrates, retinoids play key roles in the process of embryonic development and tissue regeneration ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference (RNAi) pathway, including the small interfering RNA (siRNA), microRNA (miRNA) and piwi-interacting RNA pathway, play important role in antiviral infection in animal and plant hosts. 10-14 14 The miRNAs are non-coding RNAs with 19-25 nucleotides that negatively regulate gene expression by inhibition the expression of messenger RNA (mRNA). 10 However, the mechanism of insect vector miRNAs modulate plant virus infection remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 RBSDV infection in L. striatellus could modulate the changes of miRNAs expression. 14,[18][19][20] However, the specific interaction mechanism of RBSDV with miRNAs is largely unknown. The miR184-3p was one of the most abundantly expressed miRNAs, and was up-regulated in RBSDV infected L. striatellus.…”
Section: Introductionmentioning
confidence: 99%